1999
DOI: 10.1002/(sici)1520-6327(1999)41:2<71::aid-arch3>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of actin and tubulin in an epithelial cell line from Chironomus tentans

Abstract: The morphogenetic changes in an epithelial cell line from Chironomus tentans that are evoked by molting hormones and molting hormone agonists are accompanied by transient changes in the concentration of actin and beta-tubulin protein and mRNA. As compared to controls, actin protein and mRNA concentrations increase by about 50%, whereas tubulin reaches maxima of 100% increase. The proportion between globular and filamentous actin remains constant after hormone treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Actin fragments were amplified by using the primers Act U235 (AAYTGGGAYGAYATGGARAA) and Act L667 (GCCATYTCYTGYTCRAARTC) (Fretz & Spindler 1999) and the general actin primers Actup (ATG GTN GGN ATG GGN CAR AAR) and Actdown (ATG GTN GGN ATG GGN CAR AAR) (Viray Master, Chicago, 1993). PCR was run with 15 min initial denaturation at 94 °C followed by 35 cycles of 30 sec, denaturation at 94 °C, 1 min annealing at 50 °C, and 3 min elongation at 72 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Actin fragments were amplified by using the primers Act U235 (AAYTGGGAYGAYATGGARAA) and Act L667 (GCCATYTCYTGYTCRAARTC) (Fretz & Spindler 1999) and the general actin primers Actup (ATG GTN GGN ATG GGN CAR AAR) and Actdown (ATG GTN GGN ATG GGN CAR AAR) (Viray Master, Chicago, 1993). PCR was run with 15 min initial denaturation at 94 °C followed by 35 cycles of 30 sec, denaturation at 94 °C, 1 min annealing at 50 °C, and 3 min elongation at 72 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These results were in agreement with those obtained on mammalian and other insect cell lines and confirmed that the tubulin cytoskeleton was a target for steroid hormone-triggered changes in cell shape [26,31,32,44]. Other in vitro experiments performed on Drosophila Kc cells and mouse osteoblastic cells have revealed that steroid-induced morphological modifications were also accompanied by changes in the distribution and expression level of cytoskeleton actin [24,26,[45][46][47]. It would be interesting to determine whether steroid hormones act on these two major proteins of the cytoskeleton through a common signaling pathway.…”
Section: Discussionmentioning
confidence: 53%
“…2007) together with forward and reverse primers of conserved sequence regions of actin and specific primers of the expression vector λTriplEx2 (T 7, 5TripEx, 5Triplepostslip1). Actin fragments were amplified by using the primers Act U235 and Act L667 (Fretz and Spindler 1999). and the general actin primers Actup and Actdown (Viray master, Chicago 1993).…”
Section: Methodsmentioning
confidence: 99%